Interleukin 1B proinflammatory genotypes protect against gastro-oesophageal reflux disease through induction of corpus atrophy - Ando, T (Gut, 2006)
The relationship between Helicobacter pylori infection and gastro-oesophageal reflux disease (GORD) is controversial but it is accepted that GORD is associated with increased exposure to gastric acidity. The proinflammatory interleukin (IL)-1B polymorphisms increase the risk of hypochlorhydria and gastric atrophy. We examined the association between proinflammatory cytokine gene polymorphisms, presence of gastric atrophy, and risk of GORD in H pylori positive and negative subjects in Japan. We studied 320 consecutive dyspeptic patients without peptic ulcers or cancers. GORD symptoms were scored using the Carlsson-Dent questionnaire and erosive oesophagitis was assessed endoscopically. H pylori infection was diagnosed by urea breath test, histological examination, and serology. Gastric atrophy was assessed histologically, and polymorphisms in the IL-1B, IL-10, and tumour necrosis factor alpha (TNF-A) genes were genotyped. Two hundred and eight patients were H pylori positive and 112 were negative. One hundred and eight (34%) were found to have erosive oesophagitis by endoscopic criteria (grade A: 78; grade B: 23; grade C: 6; grade D: 1). Erosive oesophagitis and GORD symptoms were significantly more common in H pylori negative compared with H pylori positive subjects (p<0.05). H pylori positive subjects were more likely to have corpus gastric atrophy than H pylori negative subjects (p<0.001). Among H pylori positive patients, those without erosive oesophagitis or GORD symptoms were significantly more likely to have corpus atrophy than subjects with erosive oesophagitis or GORD symptoms (p<0.05). Among H pylori positive patients, subjects homozygous for the proinflammatory allele IL-1B-511T had a significantly lower risk of erosive oesophagitis (odds ratio (OR) 0.06 (95% confidence interval (CI) 0.006-0.51); p=0.01) and GORD symptoms (OR 0.10 (95% CI 0.01-0.85); p=0.04) compared with those homozygous for the -511C allele, while none of the two other proinflammatory cytokine gene polymorphisms had significant correlations with erosive oesophagitis or GORD symptoms. A proinflammatory IL-1B genotype is associated with increased risk of atrophy and decreased risk of GORD in H pylori infected subjects in Japan. These data indicate that in some genetically predisposed subjects, H pylori infection may protect against GORD through induction of gastric atrophy.